2016
DOI: 10.1007/s11892-016-0769-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Diabetic Chaperome to Improve Peripheral Neuropathy

Abstract: The chaperome constitutes a broad family of molecular chaperones and co-chaperones that facilitate the folding, refolding, and degradation of the proteome. Heat shock protein 90 (Hsp90) promotes the folding of numerous oncoproteins to aid survival of malignant phenotypes, and small molecule inhibitors of the Hsp90 chaperone complex offer a viable approach to treat certain cancers. One therapeutic attribute of this approach is the selectivity of these molecules to target high affinity oncogenic Hsp90 complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 89 publications
(119 reference statements)
0
22
0
Order By: Relevance
“…The mechanisms responsible for diabetic neuropathy and potential treatments have been the subject of intense research for many years. Studies with animal models have identified a wide range of therapeutic targets for treatment of diabetic peripheral neuropathy, but translation to human subjects has not been successful [1••, 9, 10•, 11, 12••, 1319]. There are many explanations that may account for the lack of success in discovering a treatment(s) for diabetic neuropathy [20, 21••].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for diabetic neuropathy and potential treatments have been the subject of intense research for many years. Studies with animal models have identified a wide range of therapeutic targets for treatment of diabetic peripheral neuropathy, but translation to human subjects has not been successful [1••, 9, 10•, 11, 12••, 1319]. There are many explanations that may account for the lack of success in discovering a treatment(s) for diabetic neuropathy [20, 21••].…”
Section: Introductionmentioning
confidence: 99%
“…47,105,106 As such, experiments have confirmed that induction of the HSR can elicit a cytoprotective response in neurons against such glycemic/oxidative insults. 18,22 KU-32 ( Figure 5) is a novel, novobiocin-based, C-terminal inhibitor that binds Hsp90 but does not disrupt Aha1-Hsp90 interactions. As a result, KU-32 induces the HSR and increases Hsp70 levels, which elicits a cytoprotective mechanism to overcome oxidative stress, mitochondrial degeneration and, as a result, affords neuroprotection against glycemic insult without altering blood glucose levels.…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…Many pathological conditions, such as diabetes, cancer, dyslipidemia, neurodegenerative diseases, and aging can lead to a dysfunctional HSR and consequently, a loss of HSF-1 activation. 17,18 Researchers have also shown that diminished levels of Hsps (a direct result of deactivated HSF-1) can give rise to additional consequences of diabetes, 18,19 such as neuropathy, [19][20][21][22] retinopathy, 23,24 nephropathy, 25,26 cardiovascular diseases, 27,28 and so on. In contrast, it has been shown that the induction of specific Hsps by small molecules can elicit neuroprotection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPA/HSP70 has neuroprotective effects in a variety of neurological conditions. In the context of DM, several studies have shown that HSPA/HSP70 increases the ability of both neurons and Schwann cells to tolerate on-going diabetic insults by improving oxidative stress, mitochondrial function, and possibly inflammation, as recently reviewed [ 118 ]. In cultured sensory neurons, induction of HSPA/HSP70 increased the expression of the anti-oxidant enzyme superoxide dismutase 2 (SOD2).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%